Legal Protection Of Patients Injecting Silicone And Other Materials In The Penis - Zamroni Zamroni; Evita Isretno Israhadi; Megawati Barthos (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2021)
Silicone injection on the penis is the result of developments in the health sector. Efforts to provide services to patients must always apply applicable professional ethics. This relationship is prone to conflict when the parties do not carry out their roles as expected by the other party. This study aims to determine the legal regulation and protection of patients who inject silicone and other substances into the penis. This research is a normative legal research and empirical law, namely research conducted by collecting primary, secondary and tertiary legal materials. Legal materials obtained in research are presented in a more systematic writing in order to answer the problems that have been formulated